EVALUASI PEMENUHAN KEBUTUHAN RUANG PARKIR DI KAMPUS POLITEKNIK NEGERI SEMARANG: EVALUASI PEMENUHAN KEBUTUHAN RUANG PARKIR DI KAMPUS POLITEKNIK NEGERI SEMARANG - Buana, Lalu Yahya Surya; Wahjoedi; Nurhadi, Imam; Warsiti; Risman (Bangun Rekaprima, 2025)
Activities that occur in an activity center will certainly cause vehicle parking activities. Parking facilities are a very important supporting factor and require extra attention for their development in the activity center. Parking problems are something that we often encounter in various locations of educational centers, shopping centers, hospitals, factories, universities and many other places. One real example that occurs in Semarang is on the Semarang State Polytechnic campus, every day active lectures are certainly always a buildup of vehicles that cause traffic activities around the Semarang State Polytechnic campus to become dense. Therefore, an evaluation is needed to fulfill the need for parking space on the Semarang State Polytechnic campus. In evaluating the fulfillment of parking needs, Parking Characteristics on the Semarang State Polytechnic Campus with a composition of 2-wheeled and 4-wheeled vehicles with a parking duration for each type of vehicle is 425 minutes and 546 minutes with a parking index of 104% and 277%. The need for parking space that must be provided on the Semarang State Polytechnic campus with each type of vehicle is 3622.3 for 2-wheeled vehicles and 140.8 for 4-wheeled vehicles.